2021
DOI: 10.1097/jxx.0000000000000558
|View full text |Cite
|
Sign up to set email alerts
|

C19TM: A nurse practitioner and physician assistant–led telemonitoring initiative ensures timely transfer of critically ill coronavirus disease 2019 patients

Abstract: To determine the amount of static and dynamic pupil decentrations that occur during laser refractive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…APNs led telehealth innovations (Lim et al., 2020; McLachlan et al., 2021; Ross & Meier, 2021; Santos et al., 2021; Waterman, 2020) or contributed to team‐based models of telehealth care (Ambrosini et al., 2020; Blazey‐Martin et al., 2020; de Peralta et al., 2021; Israilov et al., 2020; Khairat et al., 2021; Lewis et al., 2020; Sinha et al., 2020). Four articles provided APNs with guidance on the use of telehealth (Elbarbary et al., 2020; Schroeder, 2020; Smith & Raskin, 2021; Wall‐Haas, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…APNs led telehealth innovations (Lim et al., 2020; McLachlan et al., 2021; Ross & Meier, 2021; Santos et al., 2021; Waterman, 2020) or contributed to team‐based models of telehealth care (Ambrosini et al., 2020; Blazey‐Martin et al., 2020; de Peralta et al., 2021; Israilov et al., 2020; Khairat et al., 2021; Lewis et al., 2020; Sinha et al., 2020). Four articles provided APNs with guidance on the use of telehealth (Elbarbary et al., 2020; Schroeder, 2020; Smith & Raskin, 2021; Wall‐Haas, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In hospitals, APNs were involved in telehealth programs to promote early detection and management of deteriorating patients with COVID‐19 (Santos et al., 2021), provide palliative care assessments and support (Israilov et al., 2020), and deliver follow‐up care for discharged patients with COVID‐19 (Lewis et al., 2020). In primary care, clinical nurse specialists led an innovation offering 24/7 diabetes management support to providers and developed a guidance document on managing patients with diabetes who had COVID‐19 or other illnesses (Waterman, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It not only supplements the human health resources, 67 but also provides positive and effective diagnosis and treatment effects in diagnosis and treatment 68,69 . It plays an essential and positive role in remote diagnosis and treatment, medical inoculation and postdischarge care 70–72 . They are considered to be a long‐term development role 73,74 .…”
Section: Discussionmentioning
confidence: 99%
“… 68 , 69 It plays an essential and positive role in remote diagnosis and treatment, medical inoculation and postdischarge care. 70 , 71 , 72 They are considered to be a long‐term development role. 73 , 74 Domestic medical institutions with similar occupations also reported that “assistants” played an active role in preventing and controlling the epidemic in hospitals and assisting doctors in diagnosis and treatment during the COVID‐19 epidemic.…”
Section: Discussionmentioning
confidence: 99%